Pd-promoted heteropolyacid on mesoporous zirconia as a stable and bifunctional catalyst for oxidation of thiophenes. (15th February 2022) - Ullah, Latif; Zhao, Guoying; Ma, Jian-Xin; Usman, Muhammad; Khan, Rashid; Hedin, Niklas
Graphical abstract: Highlights: Pd- x PMV/ m ZrO2 was prepared and used for synergistic oxidization of thiophenes to sulfones. A high loading of PMV and Pd gave strong B- and L-acid sites to the catalyst. The observed pseudo-first order kinetics of oxidation of thiophenes is relevant for desulfurization. The Pd-15PMV/ m ZrO2 had high conversions and TOF for the oxidation of BT/DBT. Abstract: Sulfur-containing compounds are undesirable in fossil fuels, thus stringent regulations are in place to curb their atmospheric emissions. In this context, we hypothesized and showed that acid catalysis promoted by metal particles could be used to oxidize dibenzothiophene (DBT) and benzothiophene (BT) into sulfones that, in principle, can be subsequently removed. In specific, we studied the oxidative step of catalytic oxidative desulfurization (CODS) processes using a new bifunctional catalyst based on Pd-promoted molybdovanadophosphoric acid (Pd-PMV) supported on mesoporous zirconia (Pd-PMV/ m ZrO2 ). The PMV was supported on zirconia using a one-pot sol–gel method, and the Pd nanoparticles were deposited in a subsequent step. The activity of catalyst was excellent, with high conversions >99% and a turnover frequency (TOF) value of 384 h −1 for DBT, using catalyst Pd-15PMV/ m ZrO2, which had 15-wt% loading of PMV. tert -butyl hydrogen peroxide ( t BHP) was used as an oxidant under relatively mild reaction conditions. The catalyst had both Brønsted and Lewis acid sites, and the Pd nanoparticles enhanced its synergistic catalytic performance. Up to a threshold level loading of PMV, the thermal stability of the catalysts was higher than the underlying m ZrO2 support. A high catalytic activity was maintained with only a minor loss over 10 cycles, making the catalyst promising for oxidative deep-desulfurization of liquid hydrocarbon fuels.